Characteristics and functional bacteria in a microbial consortium for rice straw lignin-degrading. (July 2021) - Xu, Congfeng; Su, Xin; Wang, Jinghong; Zhang, Fangzheng; Shen, Guinan; Yuan, Yuan; Yan, Lei; Tang, Hongzhi; Song, Fuqiang; Wang, Weidong
Graphical abstract: Highlights: Microbial consortium LDC can degrade 31.18% rice straw lignin at 30℃. High abundance (44.78%) of Anaerocolumna was first found in LDC. The expression level of AAs was significantly up-regulated at peak phase. Degradation of lignin was highly correlating with Pseudomonas and Thaurea. Abstract: The degradation of lignin is the main rate-limiting step in the bio-pulping of rice straw. A lignin-degrading bacterial consortium LDC, which can efficiently degrade lignin of reed, was screened in the early stage of our laboratory work. In present study, 7-day incubation of LDC can degrade rice straw lignin by 31.18% in mineral salt medium. The communities' structure of different incubation phases varied greatly, in which high abundance (44.78%) of Anaerocolumna was first found. The expression levels of lignin degradation enzyme class II peroxidase (AA2), vanillyl alcohol oxidase (AA4) and 1, 4-benzoquinone reductase (AA6) during peak phase (48 h) were significantly up-regulated than initial phase (24 h), increasing by 112%, 165% and 67%, respectively, and 42.86% AA2 was from Thaurea ; 100% AA4 was from Clostridium ; 62.5% AA6 was from Pseudomonas . These provide microbial resources and data support for the industrialization of rice straw bio-pulping.